EVALUATION OF SMART BRANDING TANJUNGPINANG SMART CITY STRATEGY DEVELOPMENT : EMOTIONAL, FUNCTIONAL, AND SMARTNESS VALUE - Gemilang, Reza; Sholeh, Chaereyranba; Firman, Firman; Azizi, Okky Rizki (Journal Analytica Islamica, 2025)
Tanjungpinang is one of 100 cities designated as Smart City pilot cities by the Government of the Republic of Indonesia. To support this initiative, Tanjungpinang City Government then developed Tanjungpinang Smart City Masterplan, which is directly supervised by the Ministry of Communication and Information. One of the strategies that the Tanjungpinang City Government must develop as part of this masterplan is a Smart Branding strategy that focuses on the image and brand of Tanjungpinang City. This research evaluates the development of Tanjungpinang City's Smart Branding strategy based on three core values: (1) Emotional, (2) Functional, and (3) Smartness according to the Grebosz-Krawczyk (2021) framework. The research is qualitative in nature, using a case study approach conducted in Tanjungpinang City, with data collection through interviews, observations, and literature reviews. After the data was collected, it was analyzed following the processes of reduction, display, and conclusion drawing. The results of the study indicate that the Smart Branding strategy for the city of Tanjungpinang follows three main strategies, namely (1) Smart Tourism & Seaport, (2) Tanjungpinang Investment Lounge, and (3) Smart Landmark, which are collectively outlined into 17 work programs. In terms of emotional value, cultural and thematic tourism activities are conducted to strengthen the city's image; however, the lack of direct community involvement is considered a possible improvement. In terms of functional value, the work programs implemented by the City Government demonstrate consideration and objectives to provide easy access to services for tourists and investors; however, further consideration is needed to accommodate the impact of activities on socio-environmental aspects. The value of intelligence itself can be found in the development of software such as e-Tourism and the OSS portal, as well as Green Building initiatives. In its development, the Tanjungpinang City Government must ensure that the utilization of ICT, interoperability, innovation, and sustainability can be achieved. This study ultimately identified weaknesses, namely a top-down approach and minimal community participation, which could potentially reduce community acceptance of the brand and lead to rejection. Therefore, this study recommends that the Tanjungpinang City Government strengthen community participation mechanisms, realign the use and application of technology with local needs, and ensure the appropriateness of economic, social, and environmental objectives to ensure the strength of Tanjungpinang City's Smart Branding identity.